A decision-support framework for sustainable hydrogen refueling stations under solar variability and tariff reforms - Demirci, Alpaslan; Ozturk, Zafer; Dagal, Idriss (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
The large-scale deployment of sustainable hydrogen refueling stations (HRS) faces critical barriers from siting constraints, solar resource variability, and electricity tariff reforms that reshape grid economics. While previous studies often address these drivers in isolation, they rarely capture the trade-offs of photovoltaic (PV)-electrolyzer-hydrogen storage scaling under real-world conditions. This study develops a high-resolution techno-economic-environmental framework that evaluates HRS performance under land-use limitations, solar variability, tariff reforms, and hydrogen storage autonomy scenarios. Results show that siting constraints and tariff reforms can push grid dependency above 70% and hydrogen costs up to 15.8 $/kg, whereas optimal configurations reduce the Levelized Cost of Hydrogen (LCOH) to 7.72 $/kg and cut CO2 emissions by more than 70%. These optimal cases occur where PV self-consumption remains around 55%-65%, reflecting efficient utilization and balanced operation. By contrast, oversizing PV without improving self-consumption ratio (SCR) raises curtailment to 55%. Extending storage autonomy further strengthens energy security and reduces emissions, but also lengthens payback periods, underscoring the dual nature of autonomy. Overall, the framework delivers actionable insights for policymakers and investors, linking siting constraints, solar variability, and tariff reforms to the design of resilient, cost-effective, and sustainable hydrogen infrastructures that support long-term energy security.
Keywords: Hydrogen refueling stations; Photovoltaic integration; Electricity tariff reforms; Levelized cost of hydrogen; Decision-support framework; Solar variability; POWER; SYSTEMS; Chemistry; Electrochemistry; Energy & Fuels